Seed Biopriming– A Review - Deshmukh, Amol J.; Jaiman, R. S.; Bambharolia, R. P.; Patil, Vijay A. (International Journal of Economic Plants, 2020)
There are various seed priming methods such as hydro priming, osmo priming, solid matrix priming, hormo-priming, chemo-priming, nutri-priming and biopriming being useful for enhancing the seed germination, seedling vigour and to overcome abiotic stress. Moreover to these advantages, of all priming methods only biopriming method gives an extra advantage of biotic stress management and thus gain special attention. Solubilisation or mobilization of soil macro and micronutrients, siderophore production, induction of plant growth promoting activities, induction of useful biochemicals, phytoalexin and defense-related enzymes and induced systemic resistance are the mechanisms involved in seed biopriming. Range of fungal or bacterial bio agents viz., Azotobacter, Rhizobium, Arthrobacter, Agrobacterium, Azospirillum, Enterobacter, Streptomyces, Bacillus, Burkholderia, Klebsiella, PSB, Pseudomonas fluorescence, Trichoderma viride, Trichoderma harzianum and Vesicular Arbuscular Mycorhiza, whether they are biofertilizer or biopesticide, may be useful as biopriming agents. Seed biopriming is useful in almost all the crops over the globe and is an eco-friendly substitute to chemical fungicides.